Chromosome territory relocation paradigm during DNA damage response: Some insights from molecular biology to physics. (3rd September 2017) - Fatakia, Sarosh N.; Kulashreshtha, Mugdha; Mehta, Ishita S.; Rao, Basuthkar J.
ABSTRACT: Among the many facets of DNA damage response (DDR), relocation of chromosome territories (CTs) is most intriguing. We have previously reported that cisplatin induced DDR in human dermal fibroblasts led to relocation of CTs 12, 15 from the nuclear periphery to its interior while CTs 19, 17 repositioned from the interior to its periphery. Studies of CT relocation remain nascent as we begin unraveling the role of key players in DDR to demonstrate its mechanistic basis. Consolidating our recent reports, we argue that γH2AX-signaling leads to enhanced recruitment of nuclear myosin 1 (NM1) to chromatin, which via its motor function, results in CT repositioning. Next, we invoke a novel systems-level theory that subsumed CTs as pairs, not solo entities, to present the physical basis for plasticity in interphase CT arrangement. Subsequently, we posited that our systems-level theory describes a unified physical basis for non-random positioning of CTs in interphase nuclei across disparate eukaryotes.